DUOX2-Induced Oxidative Stress Inhibits Intestinal Angiogenesis through MMP3 in a Low-Birth-Weight Piglet Model - Dongbin Zou; Yun Yang; Fengjie Ji; Renlong Lv; Tieshan Xu; Chengjun Hu (MDPI AG, 2023)
Intestinal vessels play a critical role in nutrient absorption, whereas the effect and mechanism of low birth weight (LBW) on its formation remain unclear. Here, twenty newborn piglets were assigned to the control (CON) group (1162 ± 98 g) and LBW group (724 ± 31 g) according to their birth weight. Results showed that the villus height and the activity of maltase in the jejunum were lower in the LBW group than in the CON group. LBW group exhibited a higher oxidative stress level and impaired mitochondrial function in the jejunum and was lower than the CON group in the intestinal vascular density. To investigate the role of oxidative stress in intestinal angiogenesis, H2O2 was employed to induce oxidative stress in porcine intestinal epithelial cells (IPEC-J2). The results showed that the conditioned media from IPEC-J2 with H2O2 treatment decreased the angiogenesis of porcine vascular endothelial cells (PVEC). Transcriptome analysis revealed that a higher expression level of dual oxidase 2 (DUOX2) was found in the intestine of LBW piglets. Knockdown of DUOX2 in IPEC-J2 increased the proliferation and decreased the oxidative stress level. In addition, conditioned media from IPEC-J2 with DUOX2-knockdown was demonstrated to promote the angiogenesis of PVEC. Mechanistically, the knockdown of DUOX2 decreased the reactive oxygen species (ROS) level, thus increasing the angiogenesis in a matrix metalloproteinase 3 (MMP3) dependent manner. Conclusively, our results indicated that DUOX2-induced oxidative stress inhibited intestinal angiogenesis through MMP3 in a LBW piglet model.